The receptor for urokinase type plasminogen activator polarizes expression of the protease to the leading edge of migrating monocytes and promotes degradation of enzyme inhibitor complexes (The Rockefeller University Press, 1990)
Receptor-bound urokinase-type plasminogen activator (uPA) remains associated to the surface of human monocytes for many hours. Monocytes induced to migrate in a chemotactic gradient of f-Met-Leu-Phe rapidly polarize their uPA receptors to the leading front of the cells. Receptor-bound enzyme can be inhibited by plasminogen activator inhibitor 2 (PAI-2), with a kinetics comparable to that determined for the free enzyme, and uPA/PAI-2 complexes can bind to the uPA receptor. In contrast to the active enzyme, the uPA/PAI-2 complex is rapidly cleared from the monocyte cell surface; this involves an initial cleavage of the complex at the cell surface, followed by endocytosis and degradation. These results indicate that the uPA receptor can function both to focus plasmin-mediated extracellular matrix degradation in front of migrating cells, and to target uPA/PAI-2 enzyme/inhibitor complexes for degradation; they suggest that this receptor is a key determinant in the control of uPA-catalyzed extracellular proteolysis.